Emerging macrophage-based therapies for cancer: a review of preclinical and clinical advances - Brancewicz, Jan; Kucharzewska, Paulina (Frontiers in Immunology, 2025)
Macrophages, the most abundant immune cells in many solid tumors, are no longer viewed solely as accomplices of cancer but as powerful therapeutic allies. This review charts the rapid rise of macrophage-based immunotherapies, from CD47/SIRPα checkpoint blockade and CAR-macrophages to macrophage-drug conjugates (MDCs). We emphasize emerging frontiers - RNA-based reprogramming, epigenetic modulation, small activating RNA and circRNA approaches, and macrophage-derived extracellular vesicles - that are redefining how tumor-associated macrophages can be targeted or harnessed. Distinct from earlier TAM reviews, we integrate outcomes from ongoing and completed clinical trials, highlight therapeutic platforms beyond classical depletion and polarization, and frame macrophages not only as targets but also as delivery vehicles. By spotlighting both innovative strategies and the challenges of moving them into the clinic, we aim to provide a forward-looking guide for researchers and clinicians shaping the next generation of cancer immunotherapy.